Correlation of serum Vitamin D levels and disease severity in patients with atopic dermatitis: A hospital-based, cross-sectional study from North India - Shreya Malhan; Loveleen Kaur; Maninder Kaur; Dimple Chopra; Sharang Gupta; Snehdeep Kaur (Indian Journal of Allergy Asthma and Immunology)
INTRODUCTION: Atopic dermatitis (AD) is a chronic, inflammatory relapsing, and remitting skin condition with a profound impact on the quality of life of the patient as well as the caregivers. Although its pathogenesis is multifactorial, Vitamin D is now postulated to play a complex and multifaceted role in the development and progression of AD. AIMS AND OBJECTIVES: This study was designed to determine the serum levels of Vitamin D in children with AD and to establish a correlation between serum Vitamin D levels and disease severity. MATERIALS AND METHODS: This hospital-based, cross-sectional study was conducted at the department of dermatology of a tertiary care hospital in North India over a 1-year period. Two hundred children clinically diagnosed with AD were enrolled in the study. Disease severity was determined according to the SCORing Atopic Dermatitis (SCORAD) index, and Vitamin D levels were estimated by performing an enzyme-linked immunosorbent assay technique on the blood sample taken from the study participants. RESULTS: The prevalence of AD among the pediatric patients visiting our dermatology outpatient department was 8.12%. The mean age of the study participants was 4.18 ± 3.88 years (ranging from 4 months to 16 years), and the majority of the children (74%) were <5 years of age. As per the SCORAD index, mild disease was noted in 99 (49.50%) children, followed by moderate disease in 81 (40.50%) and severe disease in 20 (10%) children. The majority of the children, i.e. 165 (82.5%) had low levels of serum Vitamin D, of which 149 (74.50%) had insufficient levels, whereas 16 (8%) had deficient levels. Sufficient Vitamin D levels were present only in 35 (17.50%) children with AD. In the study sample, there was a highly significant inverse correlation (r = -0.772, P = 0.001) between the SCORAD index and serum Vitamin D levels. It was found that a higher SCORAD index was associated with lower serum Vitamin D levels among children with AD. CONCLUSION: Thus, Vitamin D supplementation could open a new corridor for the treatment of severe and resistant AD.